Effect of Operating Temperature on Marine Fuel Oil (MFO) Quality Parameters - Nissa Atviona; Alizar Ulianas; Ihut Parulian (Universitas Pendidikan Mandalika, 2026)
Marine Fuel Oil (MFO) is a residual fuel widely used in heavy industries, whose quality is influenced by refining operating conditions. This study aims to evaluate variations in key quality parameters of MFO, namely flash point, density, and viscosity, using samples obtained from a petroleum refinery in Riau, Indonesia. Data were collected through direct observation and laboratory testing during a 10-day industrial internship period using standardized ASTM methods. The results indicated that the flash point ranged from 61.83 to 73.50 °C, density ranged from 922.7 to 928.8 kg/m³, and viscosity ranged from 132.7 to 185.0 cSt. Variations in these parameters were observed during the monitoring period. However, further statistical analysis is required to confirm the strength and significance of the relationship between operating temperature and product quality. These findings highlight the importance of consistent monitoring and control of operating conditions to maintain product quality within industrial specifications.